Dark Matter RNA: Existence, Function, and Controversy - Kapranov, Philipp; St. Laurent, Georges (Frontiers in Genetics, 2012)
The mysteries surrounding the ∼97–98% of the human genome that does not encode proteins have long captivated imagination of scientists. Does the protein-coding, 2–3% of the genome carry the 97–98% as a mere passenger and neutral “cargo” on the evolutionary path, or does the latter have biological function? On one side of the debate, many commentaries have referred to the non-coding portion of the genome as “selfish” or “junk” DNA (Orgel and Crick, 1980), while on the other side, authors have argued that it contains the real blueprint for organismal development (Penman, 1995; Mattick, 2003), and the mechanisms of developmental complexity. Thus, this question could be referred to without much exaggeration as the most important issue in genetics today.